The Application of the Omaha System in Community Rehabilitation Nursing for Patients With Stroke and Previous Falls - Fang, Xiaoqun; Jia, Shulei; Wang, Qiuyan; Liu, Huifang; Zhou, Yumei; Zhang, Lingling; Dai, Tanghua; Luo, Hui; Peng, Hui; Yuan, Jun; Zhou, Huyan (Frontiers in Neurology, 2022)
Objective: This study aimed to explore the use of the Omaha System in rehabilitation and nursing methods and the effects on patients within the community who had experienced stroke and previous falls. Methods: 42 patients were randomly divided into two groups: an experimental group (n = 21) and a control group (n = 21). Patients in the control group received routine community rehabilitation care, and patients in the experimental group received community rehabilitation care on the basis of the Omaha System. Intervention lasted for one year. The Omaha outcome score, the ability to perform activities of daily living (ADL) (measured via the Modified Barthel Index [MBI]), and the incidence of falls for each group were compared before and after the intervention. Results: After one year of intervention, the Omaha outcome score and MBI of the experimental group were higher than those of the control group; the differences were statistically significant (P < 0.05). No fall occurred in either of the two groups. Conclusion: The Omaha System can comprehensively evaluate the health problems of patients, guide nursing intervention, and quantitatively evaluate the effect of nursing intervention; it is therefore worthy of promotion.